Podoconiosis: key priorities for research and implementation. (9th November 2020) - Deribe, Kebede; Mackenzie, Charles D; Newport, Melanie J; Argaw, Daniel; Molyneux, David H; Davey, Gail
Abstract: Podoconiosis is a non-infectious tropical lymphoedema causing swelling of the lower legs. Podoconiosis is associated with stigma, depression and reduced productivity, resulting in significant socio-economic impacts for affected individuals, families and communities. It is caused by barefoot exposure to soils and affects disadvantaged populations. Evidence from the past 5 y suggests that podoconiosis is amenable to public health interventions, e.g. footwear and hygiene-based morbidity management, which reduce acute clinical episodes. Although much has been learned in recent years, advances in care for these patients and worldwide control requires further reliable and relevant research. To develop a comprehensive global control strategy, the following key research priorities are important: better understanding of the global burden of podoconiosis through extended worldwide mapping, development of new point-of-care diagnostic methods and approaches to define the presence of the environmental characteristics that contribute to the development of the condition, improving treatment through an increased understanding of the pathogenesis of dermal changes over time, improved understanding of optimal ways of providing patient care at the national level, including research to optimize behavioural change strategies, determine the optimum package of care and integrate approaches to deliver robust surveillance, monitoring and evaluation of control programmes.